2007
DOI: 10.1176/appi.ps.58.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Adverse Childhood Events Among Adults With Schizophrenia Spectrum Disorders

Abstract: The findings extend the results of research in the general population by suggesting that childhood adversity contributes to worse mental health, substance abuse, worse physical health, and poor functional outcomes in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
88
3
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 0 publications
11
88
3
4
Order By: Relevance
“…Gottfredson and Hirschi's (1990) general theory of crime, with its focus on the link between effective parental socialization and the development of self-control among offspring, would anticipate that parents who are abusive, neglectful, incarcerated, or altogether absent may be less likely to utilize positive childrearing practices and less likely to succeed in sculpting their child's self-control during their formative years (Bornstein 2002). Further research has since found significant relationships between childhood adversity and higher levels of impulsivity in clinical samples (Rosenberg et al 2007;Roy 2005).…”
Section: Impulsivitymentioning
confidence: 99%
“…Gottfredson and Hirschi's (1990) general theory of crime, with its focus on the link between effective parental socialization and the development of self-control among offspring, would anticipate that parents who are abusive, neglectful, incarcerated, or altogether absent may be less likely to utilize positive childrearing practices and less likely to succeed in sculpting their child's self-control during their formative years (Bornstein 2002). Further research has since found significant relationships between childhood adversity and higher levels of impulsivity in clinical samples (Rosenberg et al 2007;Roy 2005).…”
Section: Impulsivitymentioning
confidence: 99%
“…In bipolar disorder (BD), ACE associated with earlier onset of the disorder, worse clinical course, and higher lifetime suicidal ideation and suicide attempts (Brietzke et al, 2012;Daruy-Filho et al, 2011;McIntyre et al, 2008). In schizophrenia (SCZ), ACE increase the risk of developing the illness (Jones et al, 1994) and worsen outcome (Rosenberg et al, 2007). A number of studies demonstrated that ACE associated with more severe positive symptoms (increased hallucinations, delusions), dissociative phenomena, levels of general psychopathology, social impairment, and worse cognitive functioning (Gil et al, 2009;Holowka et al, 2003;Lysaker et al, 2001;Rosenberg et al, 2007;Ross et al, 1994;Schafer et al, 2012;Schenkel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In schizophrenia (SCZ), ACE increase the risk of developing the illness (Jones et al, 1994) and worsen outcome (Rosenberg et al, 2007). A number of studies demonstrated that ACE associated with more severe positive symptoms (increased hallucinations, delusions), dissociative phenomena, levels of general psychopathology, social impairment, and worse cognitive functioning (Gil et al, 2009;Holowka et al, 2003;Lysaker et al, 2001;Rosenberg et al, 2007;Ross et al, 1994;Schafer et al, 2012;Schenkel et al, 2005). ACE also influence brain activity in response to emotional stimuli in amygdala, hippocampus, prefrontal, and cingulate cortex, affecting GM structure and function in healthy controls (HC) and in patients with SCZ Dannlowski et al, 2012b;Dannlowski et al, 2012a;Taylor et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…About 43-52% of the women with severe mental illness have reported history of childhood sexual abuse as compared with 13-32% from general population. Similarly, 33-52% of women with psychiatric disorders reported history of childhood physical abuse as compared with 20-21% of women from general population (Briere & Elliot, 2003;Chartier, Walker, & Naimark, 2007;Cloitre, Tardiff, Marzuk, Leon, & Potera, 1996;Edwards, Holden, Felitti, & Anda, 2003;Finkelhor, Hotaling, Lewis, & Smith, 1990;Muenzenmaier, Meyer, Struening, & Ferber 1993;Mueser et al, 1998;Rosenberg, Lu, Mueser, Jankowski, & Cournos, 2007). In a report by Goodman, Rosenberg, Mueser, and Drake (1997), the childhood physical and sexual abuse rates range between 51% and 97% and variation have been shown as result of methodological issues within the studies under review.…”
Section: Introductionmentioning
confidence: 99%